2021
DOI: 10.1002/adfm.202108895
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle/Polyelectrolyte Complexes for Biomimetic Constructs

Abstract: Constructing all-aqueous systems with tailored geometries can generate a new class of biomimetic materials, a fascinating but challenging goal to achieve. Here, by taking advantage of the interfacial complexation of a polyelectrolyte (PE) and cellulose nanocrystals (CNCs), a unique interfacial PE/CNC complex is demonstrated for the stabilization of aqueous two-phase systems and for the fabrication of all-aqueous double emulsions and 3D constructs. The thickness of PE/CNC complex can be effectively adjusted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Furthermore, from the compositional aspect, PEO and P2VP blocks are biocompatible and have been widely explored for biomedical applications such as drug delivery and cancer therapy. [ 30 , 31 ] Fe is an essential element for human beings and played a key role in metabolic processes. The safety evaluation experiment (Figure S7 , Supporting Information) demonstrated that the viability of 1‐day‐old HeLa cells after 30 min treatment with Fe 3+ 0.06 ‐P2VP, Fe 3+ 0.02 ‐OCPCs, and Fe 3+ 0.06 ‐OCPCs at different Fe 3+ concentrations reached an average of 90%.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, from the compositional aspect, PEO and P2VP blocks are biocompatible and have been widely explored for biomedical applications such as drug delivery and cancer therapy. [ 30 , 31 ] Fe is an essential element for human beings and played a key role in metabolic processes. The safety evaluation experiment (Figure S7 , Supporting Information) demonstrated that the viability of 1‐day‐old HeLa cells after 30 min treatment with Fe 3+ 0.06 ‐P2VP, Fe 3+ 0.02 ‐OCPCs, and Fe 3+ 0.06 ‐OCPCs at different Fe 3+ concentrations reached an average of 90%.…”
Section: Resultsmentioning
confidence: 99%
“…1) The inherent surface tension between two immiscible phases drives the formation of the confined space of single structure MPRs and the interface coalescence. [ 30 ] Surface tension, also known as free energy cost, acts tangentially to the interface between the immiscible phases and drives the emulsion systems to form a geometry that minimizes the surface area to volume ratio, that is, a sphere. For the same reason, the interface coalescence of MPRs is a thermodynamically favored process.…”
Section: Effects Of Emulsion Templates On the Interface Characteristi...mentioning
confidence: 99%
“…22−24 Furthermore, diverse multicompartmentalized structures can be formed, allowing selective segregation of cargo within the domains. 24 While these studies demonstrate the tremendous promise of PE/NP membranes formed by interfacial complexation, the membrane growth mechanism in this process remains unknown. Most studies to date in ATPS have focused on the bulk dynamics that occur during the interfacial complexation process and have not delved deeply into the assembly mechanisms that determine membrane growth.…”
Section: Introductionmentioning
confidence: 99%
“…Membranes formed by PE/NP complexation differ in permeability from their PE/PE counterparts, and NP can be selected to impart additional functionalities. For example, PE/NP membranes can exhibit high rigidity and permeability, can exchange materials across the membrane via osmotic fluxes, and can incorporate cargo by exploiting interactions with the charged species. Furthermore, diverse multicompartmentalized structures can be formed, allowing selective segregation of cargo within the domains …”
Section: Introductionmentioning
confidence: 99%